Impact of zinc and iron, their applicability techniques, and PGRs on yield of fennel (Foeniculum vulgare) - Rolaniya, Om Prakash; Garhwal, Om Prakash; Bhateshwar, Mukesh Chand (Current Horticulture, 2025)
The experiment was conducted to find out the Impact of Zinc and Iron, Their Applicability Techniques, and Plant Growth Regulators on Growth and Yield of Fennel (Foeniculum vulgare Mill.). Rajasthan Agriculture Research Institute, Durgapura, Jaipur. during 2020-21-2021-22. The experiment consisted of 25 treatment combinations with five levels of Fertilization (Control, Soil application of ZnSO4 @ 25 kg/ha, Soil application of FeSO4 @ 50 kg/ha, foliar application of ZnSO4 @ 0.5 % and foliar application of FeSO4 @ 0.5 %) and five levels of plant growth regulators (Control, GA3 @ 50 ppm, GA3 @ 100 ppm, NAA @ 25 ppm and NAA @ 50 ppm in a factorial randomized block design with three replications. The results revealed that integration of fertilization and plant growth regulators was more effective in increasing growth and yield of fennel. The results of the study clearly indicated that application of application of ZnSO4 @ 25 kg/ha to the fennel significantly increased the plant height (145.32 cm), Number of primary branches per plant (7.08), Number of secondary branches per plant (15.83), Chlorophyll content (mg/g) at 75 DAS (1.82), Seed yield (kg /ha) (1666) and Stover yield (kg /ha) (2881) as compared to control. Similarly, plant growth regulators GA3 @ 50 ppm also significantly increased the plant height (144.20 cm), Number of primary branches per plant (7.02), Number of secondary branches per plant (15.72), Chlorophyll content (mg/g) at 75 DAS (1.83), Seed yield (kg /ha) (1648) and Stover yield (kg /ha) (2867) as compared to control.